+0  
 
0
88
6
avatar+1148 

Solve for x in the given equation \(\dfrac{\sqrt{x}}{\sqrt{3}x+\sqrt{2}} = \dfrac{1}{2\sqrt{6}x+4}\)

tertre  Mar 12, 2017

Best Answer 

 #3
avatar+75332 
+5

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [ 2*sqrt(6)*x + 4]

 

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [(2(*sqrt(6)*x + 2) ]   multiply both sides by 2

 

2sqrt (x) / [sqrt(3)*x + sqrt(2)]  = 1 / [ sqrt(6)*x + 2]  cross multiply

 

(2sqrt (x))  [ sqrt(6)*x + 2]  =  sqrt(3)*x + sqrt(2)

 

Factor  sqrt (2)  out of sqrt  sqrt(6)*x + 2

 

[2sqrt (x) ] ( [sqrt (2)] * [sqrt(3) *x + sqrt(2)] )  = [ sqrt (3)*x + sqrt(2) ]

 

2sqrt(2)* sqrt(x) [ sqrt (3)*x + sqrt(2)] = [sqrt(3)*x + sqrt(2)]

 

2sqrt(2)*sqrt(x) [ sqrt (3)*x + sqrt(2)] - [sqrt(3)*x + sqrt(2)]  = 0

 

[ sqrt (3)*x + sqrt(2)] [ 2sqrt(2)* sqrt(x) - 1 ]  = 0

 

Set both factors to 0  and either

 

sqrt (3) * x + sqrt (2) = 0  →   x  = -sqrt (2)/ sqrt(3)

But this gives a non-real result to the original problem

 

Or

 

2sqrt(2) * sqrt(x)   - 1  = 0

 

sqrt(8) * sqrt (x) = 1

 

sqrt (8x) = 1     square both sides

 

8x   = 1     divide both sides by 8

 

x = 1/8

 

 

 

cool cool cool

CPhill  Mar 12, 2017
Sort: 

6+0 Answers

 #1
avatar+1148 
0

Anyone there! Help!!!!!!!!!!!!!!!!!!!!!!!!

tertre  Mar 12, 2017
 #2
avatar
0

Solve for x:
x/(3 x^2 + 2) = 1/(24 x^2 + 16)

Cross multiply:
x (24 x^2 + 16) = 3 x^2 + 2

Expand out terms of the left hand side:
24 x^3 + 16 x = 3 x^2 + 2

Subtract 3 x^2 + 2 from both sides:
24 x^3 - 3 x^2 + 16 x - 2 = 0

The left hand side factors into a product with two terms:
(8 x - 1) (3 x^2 + 2) = 0

Split into two equations:
8 x - 1 = 0 or 3 x^2 + 2 = 0

Add 1 to both sides:
8 x = 1 or 3 x^2 + 2 = 0

Divide both sides by 8:
x = 1/8 or 3 x^2 + 2 = 0

Subtract 2 from both sides:
x = 1/8 or 3 x^2 = -2

Divide both sides by 3:
x = 1/8 or x^2 = -2/3

Take the square root of both sides:
x = 1/8 or x = i sqrt(2/3) or x = -i sqrt(2/3)

x/(3 x^2 + 2) ⇒ 1/(8 (2 + 3 (1/8)^2)) = 8/131
1/(24 x^2 + 16) ⇒ 1/(16 + 24 (1/8)^2) = 8/131:
So this solution is correct

x/(3 x^2 + 2) ⇒ -(i sqrt(2/3))/(2 + 3 (-i sqrt(2/3))^2) = ∞^~
1/(24 x^2 + 16) ⇒ 1/(16 + 24 (-i sqrt(2/3))^2) = ∞^~:
So this solution is incorrect

x/(3 x^2 + 2) ⇒ (i sqrt(2/3))/(2 + 3 (i sqrt(2/3))^2) = ∞^~
1/(24 x^2 + 16) ⇒ 1/(16 + 24 (i sqrt(2/3))^2) = ∞^~:
So this solution is incorrect

The solution is:
Answer: |x = 1/8

Guest Mar 12, 2017
 #3
avatar+75332 
+5
Best Answer

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [ 2*sqrt(6)*x + 4]

 

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [(2(*sqrt(6)*x + 2) ]   multiply both sides by 2

 

2sqrt (x) / [sqrt(3)*x + sqrt(2)]  = 1 / [ sqrt(6)*x + 2]  cross multiply

 

(2sqrt (x))  [ sqrt(6)*x + 2]  =  sqrt(3)*x + sqrt(2)

 

Factor  sqrt (2)  out of sqrt  sqrt(6)*x + 2

 

[2sqrt (x) ] ( [sqrt (2)] * [sqrt(3) *x + sqrt(2)] )  = [ sqrt (3)*x + sqrt(2) ]

 

2sqrt(2)* sqrt(x) [ sqrt (3)*x + sqrt(2)] = [sqrt(3)*x + sqrt(2)]

 

2sqrt(2)*sqrt(x) [ sqrt (3)*x + sqrt(2)] - [sqrt(3)*x + sqrt(2)]  = 0

 

[ sqrt (3)*x + sqrt(2)] [ 2sqrt(2)* sqrt(x) - 1 ]  = 0

 

Set both factors to 0  and either

 

sqrt (3) * x + sqrt (2) = 0  →   x  = -sqrt (2)/ sqrt(3)

But this gives a non-real result to the original problem

 

Or

 

2sqrt(2) * sqrt(x)   - 1  = 0

 

sqrt(8) * sqrt (x) = 1

 

sqrt (8x) = 1     square both sides

 

8x   = 1     divide both sides by 8

 

x = 1/8

 

 

 

cool cool cool

CPhill  Mar 12, 2017
 #4
avatar+4155 
+1

Hey CPhill, I was trying to follow the Guest's work and it looks like the first step was square every term. I was just wondering is that really allowed??

hectictar  Mar 13, 2017
 #5
avatar+75332 
0

To be honest, hectictar, I wondered about that, too.....maybe the Guest knows something that we don't......!!!!

 

 

cool cool cool

CPhill  Mar 13, 2017
 #6
avatar+75332 
+5

After looking at this problem again....I see  that it's really very easy to solve

 

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [ 2*sqrt(6)*x + 4]   

 

sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [ (2)[sqrt(6)*x + 2 ] ]   multiply both sides by 2

 

2sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 / [ sqrt(6)*x + 2]

 

Factor  sqrt (2)  out of  sqrt(6)*x + 2    =   sqrt(2) [ sqrt(3)*x + sqrt(2)]  

 

2sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 /  (sqrt(2) [ sqrt(3)*x + sqrt(2)] )

 

Multiply both sides by sqrt(2)

 

sqrt(2)*2sqrt(x) / [ sqrt(3)*x + sqrt(2) ] = 1 /  [ sqrt(3)*x + sqrt(2)]

 

Since the denominators  are the same, we can solve for the numerators

 

sqrt (2)* 2sqrt(x) = 1

 

2sqrt(2)sqrt(x)  = 1

 

sqrt(8)sqrt(x)  = 1

 

sqrt (8x)  = 1    square both sides

 

8x  = 1  →   x  = 1/8

 

cool cool cool

CPhill  Mar 13, 2017

9 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details